Autumn sonata [videorecording (DVD)] - Bergman, Ingmar, 1918-2007; Bergman, Ingmar, 1918-2007; Bergman, Ingrid, 1915-1982; Ullmann, Liv; Nyman, Lena (Criterion collection, 2013)
An internationally famous concert pianist visits her grown daughter after a long absence.